Genetic variability, heritability and correlation analysis for some characters in hybrids of the mulberry silkworm, Bombyx mori L. - Ahsan, Md Kamrul; Rahman, Sowdagar Mahfuzar; Haque, Md Tajimul (Journal of Life and Earth Science, 2011)
Genetic variability, heritability and correlation analysis for some important economic characters in 35 hybrids of the silkworm, Bombyx mori L. have been investigated. Higher heritability values were recorded for effective rate of rearing by number (ERRn), followed by estimated cocoon yield per 100 dfls (ECY), weight of mature larvae (WML), filament length (FL) and effective rate rearing by weight (ERRw). Furthermore, characters such as FL, ERRn, ERRw and ECY showed higher genetic advance coupled with higher heritability values, indicating the importance of additive gene effect of these characters. The genotypic correlations were higher than the phenotypic correlations for all the characters under study. These low phenotypic correlations could be due to a modifying effect of environment of the association of characters at genotypic level. Most of the characters showed positive significant correlation to each other except ERRn and ERRw pair at phenotypic level. Therefore, proper attention should be given to these characters, especially WML, FL and ECY, in selection programmes for genetic gain in B. mori. Key words: Genetic variability; heritability; correlation; economic characters; B. mori. DOI: 10.3329/jles.v5i0.7349 J. Life Earth Sci., Vol. 5: 43-46, 2010